Genome‐wide nucleotide diversity of hatchery‐reared Atlantic and Mediterranean strains of brown trout Salmo trutta compared to wild Mediterranean populations1. Issue 6 (25th September 2016) - Leitwein, M.; Gagnaire, P.‐A.; Desmarais, E.; Guendouz, S.; Rohmer, M.; Berrebi, P.; Guinand, B.
Abstract : A genome‐wide assessment of diversity is provided for wild Mediterranean brown trout Salmo trutta populations from headwater tributaries of the Orb River and from Atlantic and Mediterranean hatchery‐reared strains that have been used for stocking. Double‐digest restriction‐site‐associated DNA sequencing (dd‐RADseq) was performed and the efficiency of de novo and reference‐mapping approaches to obtain individual genotypes was compared. Large numbers of single nucleotide polymorphism (SNP) markers with similar genome‐wide distributions were discovered using both approaches (196 639 v. 121 016 SNPs, respectively), with c. 80% of the loci detected de novo being also found with reference mapping, using the Atlantic salmon Salmo salar genome as a reference. Lower mapping density but larger nucleotide diversity ( π ) was generally observed near extremities of linkage groups, consistent with regions of residual tetrasomic inheritance observed in salmonids. Genome‐wide diversity estimates revealed reduced polymorphism in hatchery strains ( π = 0·0040 and π = 0·0029 in Atlantic and Mediterranean strains, respectively) compared to wild populations ( π = 0·0049), a pattern that was congruent with allelic richness estimated from microsatellite markers. Finally, pronounced heterozygote deficiency was found in hatchery strains (Atlantic F IS = 0·18; Mediterranean F IS = 0·42), indicating that stocking practices may affect the genetic diversity in wild populations. These new genomic resources will provide important tools to define better conservation strategies in S. trutta .